Improving Students’ Writing Skills Using Grammarly Application Media - Talan, Leticia Laurenca Anjeli; Dangin, Dangin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
As technology advances, education becomes more sophisticated and the level becomes more advanced. The aim of this research is to determine the improvement in students' writing skills using the Grammarly application media. This research is classified as quantitative research using Class Action Research (CAR) design. The participants of this research were 32 students from SMP N 2 GODEAN. Data were collected through pre-test, progress-test and post-test. This study reveals how the media application, namely grammarly, can improve students' writing skills. Research data analysis is descriptive quantitative. The research results show students' writing skill improved by using Grammarly. This application is assumed very useful for use in class and helps students focus more on the material being studied. Keywords: Grammarly Application, Writing skills